TECHNOLOGY OF SMOOTHIE BASED ON WALNUT NUT BEVERAGE WITH ADDITION OF BANANA AND COCOA POWDER - Янчик, Мария; Савчук, Юрий (SWorldJournal, 2021)
Abstract. This article substantiates the choice of raw materials of plant origin for the preparation of a smoothie based on a beverage from walnut kernels with the addition of banana and cocoa powder.